A Screen-Printed Electrode Modified With Graphene/Co3O4 Nanocomposite for Electrochemical Detection of Tramadol - Aflatoonian, Mohammad Reza; Tajik, Somayeh; Aflatoonian, Behnaz; Beitollahi, Hadi; Zhang, Kaiqiang; Le, Quyet Van; Cha, Joo Hwan; Jang, Ho Won; Shokouhimehr, Mohammadreza; Peng, Wanxi (Frontiers in Chemistry, 2020)
In this paper, graphene (Gr)/Co3O4 nanocomposite was synthesized and utilized for the development of a novel electrochemical sensor to detect tramadol. Tramadol determination was examined by linear sweep voltammetry, differential pulse voltammetry, cyclic voltammetry, and chronoamperometry on Gr/Co3O4 nanocomposite-modified screen-printed electrode (Gr/Co3O4/SPE) in phosphate-buffered saline (PBS). Under the optimized condition, the detection limit of tramadol is 0.03 μM (S/N = 3) in the linear ranges of 0.1–500.0 μM. Furthermore, Gr/Co3O4/SPE was satisfactorily utilized to detect tramadol in tramadol tablet and urine specimens.